Influência do suporte social e capacidade funcional na adesão ao tratamento antirretroviral de pessoas com 50 anos ou mais - Oliveira, Tyane Mayara Ferreira (2019)
The study aims to analyze the influence of social support and degree of functional capacity on adherence to antiretroviral treatment of people living with HIV/aids aged 50 or older. It is a quantitative, cross-sectional and correlational research with descriptive and analytical components. It was performed with 265 people living with HIV/aids, from December 2018 to February 2019, in a referral hospital for infectious diseases in Fortaleza/CE. Data were compiled and analyzed using the Statistical Package for the Social Sciences (SPSS), version 24.0, using descriptive statistics techniques, aggregated indices for the identification of social support levels, cluster analysis, Kruskal-Wallis, chi-square and Fisher. The project was submitted to the Research Ethics Committee of the Federal University of Ceará and the Hospital Institution where the data collection took place, being approved in both. The ethical and legal aspects involving research with human beings were respected, according to Resolution 466∕2012 of the National Health Council of Brazil. The sample consisted predominantly of patients aged 50 to 60 years (77%), male (67.9%), heterosexual (65.3%), single or divorced (58.1%), illiterate or with incomplete elementary school (47.2%), with monthly family income of up to one minimum wage (55.8%) and living alone (33.2%). 82.6% acquired the virus sexually, 81.2% had between one and 20 years of infection, 56.6% had used Antiretroviral Therapy (ART) for at least 11 years, and presented as the most present opportunistic infection tuberculosis (18.9%). There was an increase between the number of patients with undetectable viral load between the first visit (18.9%) and the last visit (66%), as well as the high TCD4 lymphocyte count at the last visit (51.3%), as opposed to first (15.8%). Most of the people surveyed were adherent to ART. The classification regarding the perception of social support was median and the main sources of reported support were friends, followed by health professionals and children. Regarding functional capacity, a considerable percentage of the sample was classified as independent to perform basic and instrumental activities of daily living. Age, presence of depression, availability of emotional social support and functional capacity were statistically related to adherence to ART. It is concluded, therefore, that there is a relationship between epidemiological, clinical, emotional social support and functional capacity factors regarding the process of adherence to ART among people aged 50 years or older.